Technical Study on Retirement and Pensions Projections of the Central Government - Planning Commission (Planning Commission Government of India, 2002)
This technical study by Dr. Pronab Sen and Sibani Swain examines the Central Government's salary and pension liabilities, with a focus on fiscal sustainability following the Fifth Central Pay Commission (FCPC) recommendations. The analysis highlights rising pension liabilities, which increased from 0.24% of GDP in 1980-81 to 0.73% in 1999-2000, accounting for 5.7% of total revenue expenditure in 1999-2000. Employment projections, including the Prime Minister’s proposed 10% reduction over five years, are scrutinized, revealing that assumed attrition rates may be overstated and inconsistent with empirical data. Pension trends show abrupt increases aligned with Pay Commission revisions, and future liabilities are projected to grow at 7.5% annually, surpassing prior estimates of 3.8%. The study underscores the need for a robust data framework, systematic tracking of retirees, and differentiated accounting for various pension categories to ensure accurate projections. Recommendations advocate evidence-based workforce and pension management strategies to enhance fiscal planning, reduce risks, and support sustainable government financial practices. The research provides critical insights for policymakers to address the structural challenges in managing Central Government employment and pension obligations.
Planning Commission Government of India January, 2002
Keywords: Central Government; Pension Liabilities; Salary Expenditure; Fiscal Sustainability; Employment Projections; Attrition Rates; Pay Commission; Pension Growth; Demographic Shifts; Workforce Management; Financial Forecasting; Policy Recommendations